2021
DOI: 10.3389/fonc.2021.642144
|View full text |Cite
|
Sign up to set email alerts
|

Complement C1q (C1qA, C1qB, and C1qC) May Be a Potential Prognostic Factor and an Index of Tumor Microenvironment Remodeling in Osteosarcoma

Abstract: The tumor microenvironment (TME) has important effects on the tumorigenesis and development of osteosarcoma (OS). However, the dynamic mechanism regulating TME immune and matrix components remains unclear. In this study, we collected quantitative data on the gene expression of 88 OS samples from The Cancer Genome Atlas (TCGA) database and downloaded relevant clinical cases of OS from the TARGET database. The proportions of tumor-infiltrating immune cells (TICs) and the numbers of immune and matrix components w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 31 publications
2
42
1
Order By: Relevance
“…6, 11, 12 In a previous study, sarcoma was also classified in the group in which stronger expression of the classical and alternative pathway genes was associated with longer survival ( Roumenina et al, 2019 ). In a recent analysis, complement classical pathway genes C1QA, C1QB, C1QC were proved to be protective factors for survival in osteosarcoma ( Chen et al, 2021 ). The results have suggested that while the lectin pathway facilitates progression and immunosuppression of sarcoma ( Magrini et al, 2021 ), the classical pathway might have played more of a tumoricidal role and thus benefits patients’ survival.…”
Section: Discussionmentioning
confidence: 99%
“…6, 11, 12 In a previous study, sarcoma was also classified in the group in which stronger expression of the classical and alternative pathway genes was associated with longer survival ( Roumenina et al, 2019 ). In a recent analysis, complement classical pathway genes C1QA, C1QB, C1QC were proved to be protective factors for survival in osteosarcoma ( Chen et al, 2021 ). The results have suggested that while the lectin pathway facilitates progression and immunosuppression of sarcoma ( Magrini et al, 2021 ), the classical pathway might have played more of a tumoricidal role and thus benefits patients’ survival.…”
Section: Discussionmentioning
confidence: 99%
“…Cytotoxic T-lymphocyte-associated protein 4 binds to this protein to negatively regulate T-cell activation and diminishes the immune response 49 C1QA complement C1q A chain C1QA encodes C1r and C1s associated proteins to yield the first component of the serum complement system. The deficiency is related to lupus erythematosus and glomerulonephritis 50 ITGB2 integrin subunit beta 2 This gene encodes an integrin beta chain. The encoded protein mainly affects immune response.…”
Section: Resultsmentioning
confidence: 99%
“…The abnormal methylation of C1QA is also associated with the progression of thyroid cancer and is a potential biomarker (52). In osteosarcoma, the expression level of C1QA is positively correlated with patient survival time and levels of macrophage and CD8 cell in the tumor immune microenvironment (53). It has been reported that 3 human C1Q genes are closely bundled on chromosome 1 (C1QA-C1QC-C1QB) and their basal and IFNg-stimulated expression, largely restricted to macrophages and dendritic cells (54).…”
Section: Discussionmentioning
confidence: 99%